Arachidonic Acid and Docosahexaenoic Acid Metabolites in the Airways of Adults With Cystic Fibrosis: Effect of Docosahexaenoic Acid Supplementation - Teopompi, Elisabetta; Risé, Patrizia; Pisi, Roberta; Buccellati, Carola; Aiello, Marina; Pisi, Giovanna; Tripodi, Candida; Fainardi, Valentina; Clini, Enrico; Chetta, Alfredo; Rovati, G. Enrico; Sala, Angelo (Frontiers in Pharmacology, 2019)
Cystic fibrosis (CF) is an autosomal recessive disorder, caused by genetic mutations in CF transmembrane conductance regulator (CFTR) protein. Several reports have indicated the presence of specific fatty acid (FA) alterations in CF patients, most notably decreased levels of plasmatic and tissue docosahexaenoic acid (DHA), the precursor of Specialized Pro-resolving Mediators (SPMs). We hypothesized that an imbalance between arachidonic acid (AA)- and DHA-derived products could contribute to the chronic pulmonary inflammation observed in CF subjects. Sputum samples from CF and Chronic Obstructive Pulmonary Disease (COPD) subjects were collected and analyzed by LC/MS/MS and blood FAs were profiled by gas chromatography upon lipid extraction and transmethylation. As compared to COPD patients, CF subjects showed increased concentrations of leukotriene B4 (LTB4), prostaglandin E2 (PGE2), and 15-hydroxyeicosatetraenoic acid (15-HETE), while the concentrations of DHA metabolites were not different in the two groups. After DHA supplementation, not only DHA/AA ratio and highly unsaturated fatty acid (HUFA) index were significantly increased (p < 0.05), but CF subjects showed a significant reduction in LTB4 and 15-HETE together with a tendency toward a decrease in PGE2 and an increase in 17-hydroxy-docosahexaenoic acid (17OH-DHA) levels. At the end of the washout period, LTB4, PGE2, 15-HETE, and 17OH-DHA tended to recover baseline values. As compared to baseline, 15-HETE/17OH-DHA ratio significantly changed after supplementation (p < 0.01). Our results showed that in CF patients an impairment in FA metabolism, characterized by increase in AA metabolites and decrease in DHA, was partially corrected by DHA supplementation